Pre-analytical stability of sorbitol dehydrogenase in equine heparinized plasma. (August 2021) - Fouché, N.; Oesch, S.; Gerber, V.; Richter, H.; Howard, J.; Peters, L.M.
Highlights: Plasma sorbitol dehydrogenase (SDH) is useful in assessing equine hepatic function. Equine plasma SDH values are stable regardless of storage temperature for 4 h. Immediate post-collection plasma separation and refrigeration is recommended. At 4 °C, activity of plasma SDH is suitable for analysis for 24 h. For SDH, plasma storage for >4 h at room temperature or −20 °C is not recommended. Abstract: Sorbitol dehydrogenase (SDH) activity is one of the most sensitive and specific markers for hepatocellular injury in horses, but its reported lability makes it impractical for use in many clinical settings. To date, stability of SDH in equine samples has only been evaluated in a limited number of studies in serum samples of horses with activities within reference intervals. The objective of the study was to determine pre-analytical stability of equine SDH activity in heparinized plasma stored at different temperatures for up to 72 h. Twenty client-owned horses admitted to a veterinary teaching hospital for any reason were included in the study. Blood samples collected in lithium-heparin tubes were immediately centrifuged and SDH activity was analyzed within 1 h of collection (T0). Aliquots of plasma were stored at room temperature, 4 °C and −20 °C and SDH activity was re-analyzed after 4 h (T4), 24 h (T24) and 72 h (T72). A significant difference from values measured at T0 was found for samples stored at room temperature ( P = 0.022) and −20 °C ( P < 0.001), but not at 4 °C. The activity of SDH was within ±20% of that measured at T0 for all samples under all temperature conditions stored for 4 h, and for all samples stored at 4 °C for 24 h. Bland–Altman plots revealed narrow limits of agreement at T4 for all storage temperatures and at T24 for samples stored at 4 °C. The mean absolute percentage error and 95th percentile of the absolute percentage error were lower for samples stored at 4 °C than those stored at room temperature or −20 °C. The activity of SDH has adequate stability for 4 h regardless of storage temperature and 24 h if stored at 4 °C across a wide range of values. Knowledge of the pre-analytical stability of SDH may permit its broader use in assessing hepatic disorders in horses.